2012
DOI: 10.1111/j.1742-6723.2011.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic hip dislocations: Is relocation in the emergency department by emergency medicine staff better?

Abstract: There was no difference between EM and orthopaedics in the proportion of hips successfully relocated or complications in the ED; however, EM patients were discharged much sooner, with important resource implications. Procedures carried out in the OT were more successful than in the ED but resulted in prolonged hospital stays and were associated with more complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
4
8
0
Order By: Relevance
“…However, sedation in the ER can lead to “oversedation” and airway obstruction, and has a lower success rate than reduction under general anesthesia in the OR ( Frymann et al 2005 ; Dela Cruz et al 2014 ). In the present study, we found a mean surgical delay of 2.5 h for fast-track cases, which is comparable to surgical delay times achieved for hip arthroplasty reduction in the ER reported by several authors ( Frymann et al 2005 ; Gagg et al 2009 ; Lawrey et al 2012 ). Surgical delay for both the fast-track pathway cases and the regular pathway cases in our study was shorter than what has been reported previously for surgical delay until reduction in the OR ( Frymann et al 2005 , Wan et al 2008 , Gagg et al 2009 ).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…However, sedation in the ER can lead to “oversedation” and airway obstruction, and has a lower success rate than reduction under general anesthesia in the OR ( Frymann et al 2005 ; Dela Cruz et al 2014 ). In the present study, we found a mean surgical delay of 2.5 h for fast-track cases, which is comparable to surgical delay times achieved for hip arthroplasty reduction in the ER reported by several authors ( Frymann et al 2005 ; Gagg et al 2009 ; Lawrey et al 2012 ). Surgical delay for both the fast-track pathway cases and the regular pathway cases in our study was shorter than what has been reported previously for surgical delay until reduction in the OR ( Frymann et al 2005 , Wan et al 2008 , Gagg et al 2009 ).…”
Section: Discussionsupporting
confidence: 87%
“…This is possibly due to the large variation in logistic setup between different institutions: some dislocations are reduced in the ER, while others are admitted to the hospital and reduced in the OR under general anesthesia. The LOS following the fast-track pathway for reduction of a dislocated hip arthroplasty reported in our study was shorter than the LOS reported by Lawrey et al (2012) for patients reduced in the OR, and it was similar to the LOS for dislocations reduced by orthopedic service doctors in the ER.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations